Detection of silent myocardial ischemia in asymptomatic patients with diabetes: results of a randomized trial and meta-analysis assessing the effectiveness of systematic screening - Lièvre, Michel M; Moulin, Philippe; Thivolet, Charles; Rodier, Michel; Rigalleau, Vincent; Penfornis, Alfred; Pradignac, Alain; Ovize, Michel (Current controlled trials in cardiovascular medicine, 2011)
Background Most guidelines recommend a systematic screening of asymptomatic high risk patients with diabetes for silent ischemia, but the clinical benefit of this strategy has not been demonstrated compared with the simple control of cardiovascular risk factors. We sought to determine whether referring asymptomatic diabetic patients for screening of silent ischemia decreases the risk of cardiovascular events compared with usual care. Methods DYNAMIT was a prospective, randomized, open, blinded end-point multicenter trial run between 2000 and 2005, with a 3.5 year mean follow-up in ambulatory care in 45 French hospitals. The study included 631 male and female with diabetes aged 63.9 ± 5.1 years, with no evidence of coronary artery disease and at least 2 additional cardiovascular risk factors, receiving appropriate medical treatment. The patients were randomized centrally to either screening for silent ischemia using a bicycle exercise test or Dipyridamole Single Photon Emission Computed Tomography (N = 316), or follow-up without screening (N = 315). The main study end point was time to death from all causes, non-fatal myocardial infarction, non-fatal stroke, or heart failure requiring hospitalization or emergency service intervention. The results of a meta-analysis of DYNAMIT and DIAD, a similar study, are also presented. Results The study was discontinued prematurely because of difficulties in recruitment and a lower-than expected event rate. Follow-up was complete for 98.9% patients regarding mortality and for 97.5% regarding the main study end point. Silent ischemia detection procedure was positive or uncertain in 68 (21.5%) patients of the screening group. There was no significant difference between the screening and the usual care group for the main outcome (hazard ratio = 1.00 95%CI 0.59 to 1.71). The meta-analysis of these and DIAD results gave similar results, with narrower confidence intervals for each endpoint. Conclusions These results suggest that the systematic detection of silent ischemia in high-risk asymptomatic patients with diabetes is unlikely to provide any major benefit on hard outcomes in patients whose cardiovascular risk is controlled by an optimal medical treatment. Trial registration ClinicalTrials.gov: NCT00627783